Isothermal titration calorimetric study of the ionic liquid solutions in alcohols in extreme dilutions: an investigation of ion-solvent interactions - Rai, Gitanjali; Jain, Preeti; Kumar, Anil (Journal of Solution Chemistry, 2016)
In this work an effort has been made to show the effect of an alcohol-rich environment on imidazolium-based ionic liquids at 298.15 K using an isothermal titration calorimeter. It is divulged from this study that the thermal behavior expressed in terms of excess partial molar enthalpy, \( H_{\text{IL}}^{\text{E}} \), of ionic liquids in various linear alcohols is governed by the increasing hydrophobicity of the residual alkyl group attached to the cation of an ionic liquid and to the alcohol molecules. An interesting observation about the systems consisting of ethylated residuals on both the cations of the ionic liquid and the alcohol molecules is that these systems do not follow the trend exhibited by other ionic liquid–alcohol systems. Interesting information on ionic interactions is obtained by using a simple methodology that gives the enthalpic interaction parameter \( H_{{I{\text{L - IL}}}}^{\text{E}} \).
Keywords: Ionic liquidsAlcoholsExcess enthalpyIsothermal titration calorimeter